O sertão traduzido: estudo dos marcadores culturais do domínio ecológico, na tradução de Os Sertões para a língua espanhola - Nascimento, Geovanio Silva do (2018)
Os Sertões, from Euclides da Cunha, enjoys wide recognition by part of the literary criticism and it is considered one of the most representative books of Brazilian literature. That occurs, mostly, due to the its subject matter, the War of Canudos, and the way the author has built his narrative, allowing the book to be studied through various fields of knowledge. The prestige of “Os Sertões” reveals itself in the interest it has aroused in readers outside Brazil, resulting the translation to various languages, among them Spanish, which was the first foreign language to which the book was translated. This dissertation aimed at performing a study on the Cultural Markers present in Da Cunha’s book Os Sertões (1984[1902]) as well as investigating how those CMTs were translated to Spanish (SANTOS, 1980). The research starts with a discussion on the writing process of the book, highlighting the contacts and the research sources of the author, setting up his works and his critical fortune, such as Santana (1995), Valente (2007; 1996), Galvão (1977; 1981; 1984), Medeiros (2009), among others. Then, it was discussed the vocabulary of Euclides Os Sertões, starting from some studies already done (GALVÃO, 1985; SANTOS, 1980; ZACHARIAS, 2001). The theoretical- methodological cutout was done from notions, definitions and concepts of Corpus Linguistics and Translation (BAKER, 1993; SARDINHA, 2002; 2004; CAMARGO 2007; 2008), Cultural Domains, Cultural Markers (NIDA, 1945; AUBERT, 2006a; 2006b; 2008; CAMARGO, 2008; e REICHMAN; ZAVAGLIA, 2014) and Translation Modalities (AUBERT, 1998; 2006a; 2006b). Based on the precepts of Corpus Linguistics, it was compiled a paralleled corpus formed by the Portuguese version of Os Sertões and its translation to Spanish in order to search for the CMTs candidates and their respective translation components. For the corpus treatment and analysis, it was used, in this investigative work, some computer softwares, mainly the WordSmith Tools 7.0, their tools and utilities like Concord, Keyword, Wordlist, Text convert and Aligner. The results were the compilation of 95 Cultural Markers from the Portuguese version of the book, their Spanish translation correspondents and the identification of the Translation Modalities. Those data were organized in lexicographic files, created to this end, and which present definition and subscriptions. Those data served as a parameter for the analysis, which turned out to be a trend in the use of one single type of Translation Modality for the Cultural Markers with sporadic possibilities of variation, causing the use of only one variable in the translation of those lexical unities, in general, with a little possibility of variation.